Composition, functional components, and physical characteristics of grain from staygreen and senescent sorghum lines grown under variable water availability. Issue 5 (30th June 2018) - Emendack, Yves; Burke, John; Bean, Scott; Wilson, Jeff; Hayes, Chad; Laza, Haydee
Abstract: Background and objectives: The inclusion of sorghum into human food and feed is limited by its low digestibility compared to corn, due to the presence of high total kafirin levels in sorghum grain. Water stress after pollination reduced grain filling, affecting the grain composition, grain functional components, and grain physical characteristics. Sorghum lines possessing the staygreen trait continue to fill their grain under postflowering water deficit. Understanding the environmental effect on the grain nutritional composition and grain physical characteristics of staygreen and senescent sorghum lines will be critical for breeders when selecting traits. This research evaluated a diverse group of staygreen and senescent sorghum lines subjected to full, preflowering water deficit, and postflowering water deficit irrigations. Findings: Staygreen lines had significantly higher levels of total protein and total kafirin, but lower total starch than senescent types. Higher kafirin level was linked to kernel hardness, and this level increased under water deficit. There were no differences between staygreen and senescent sorghum lines in protein digestibility, fermentation efficiency, kafirin per percent protein, kernel hardness, kernel weight, and kernel diameter irrespective of irrigation treatment. Conclusions: The nutritional quality and digestibility of sorghum grains were affected by the environment and varies across lines and cultivars. Higher total kafirin level in grains reduces digestibility and impedes energy utilization by interfering with starch digestion. Staygreen lines had significantly higher levels of total protein and total kafirin, but lower total starch than senescent types. Significance and novelty: With considerable variability in grain digestibility and feeding value among sorghum cultivars, the effect of environments on grain nutritional composition and other quality traits should be considered to match the user's purpose.